Development of conceptual remotely operated vehicle (ROV) for pre-surveillance checklist / Remi Glemet ... [et al.] - Glemet, Remi; Jamil, Nordiana; Mohamid Salih, Noorazlina; Mohd Said, Mohd Shahrizan (2019)
Remotely Operated Vehicle or also known as ROV in short is a computer-controlled system operating underwater. It can be controlled from far from on the ship or offshore. This remotely operated underwater vehicle can move in many ways based on its design and application. It can move, drifts, dives or glides from the sea surface to ocean depth controlled and operate from a far. Usually it is designed to operate under sea level and come with basic design. With the latest technologies, it is built with more efficient design that can operate better beyond any level of the sea. Other than that, remotely operated vehicle allows scientist to conduct experiment to collect data elsewhere in the deep ocean and controlled it on the surface or on a ship. They usually used for commercial purpose. Oil drilling and subsea drilling companies use the assistance of remotely operated underwater vehicle for the purpose of checking the appropriate oceanic area to suit their business necessity. Some of them are designed for research and exploring purposes. Additionally, military also used this autonomous underwater vehicle technology to surveillance what's going on in the ocean to find out whether there are any booby-traps set in the ocean floor. When it comes to military usage, an ROV is the best scouting technology that can be used for underwater purposes. However, ROV can be used for hobby by peoples who want to surveillance the deep water or fish.